Anne of Green Gables [videorecording (DVD)] : the sequel - Sullivan, Kevin, 1955-; Follows, Megan; Dewhurst, Colleen; Hamilton, Patricia; Crombie, Jonathan; Converse, Frank, 1938-; Hiller, Wendy, 1912-2003; Montgomery, L. M. (Lucy Maud), 1874-1942 (Sullivan Entertainment, 2002)
Anne leaves Green Gables and Gilbert Blythe's proposal of marriage for a teaching position. When she returns, she finds Gilbert ill with a scarlet fever and is forced to re-evaluate her true feelings for him.